2008
DOI: 10.1002/ijc.23463
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression changes during HPV‐mediated carcinogenesis: A comparison between an in vitro cell model and cervical cancer

Abstract: We used oligonucleotide microarrays to investigate gene expression changes associated with multi-step human papillomavirus type 16 (HPV16)-mediated carcinogenesis in vitro. Gene expression profiles in 4 early passage HPV16-immortalized human keratinocyte (HKc) lines derived from different donors were compared with their corresponding 4 late-passage, differentiation-resistant cell lines, and to 4 pools of normal HKc, each composed of 3 individual HKc strains, on Agilent 22 k human oligonucleotide microarrays. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
94
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(104 citation statements)
references
References 49 publications
8
94
1
Order By: Relevance
“…Overexpression of SIX1 is observed in various types of cancer such as hepatocellular carcinoma (Ng et al, 2006), breast cancer (Kumar, 2009), ovarian cancer (Behbakht et al, 2007) and cervical cancer (Wan et al, 2008). In addition, overexpression of SIX1 is likely to be related to progression, invasion or metastasis in some cancers such as hepatocellular carcinoma (Ng et al, 2006) and breast cancer (Coletta et al, 2008), although understanding of the molecular mechanisms of SIX1 Figure 4 (a) ZEB1 and SNAI1 mRNA (left, bar graphs) and protein (right, western blotting) expression level in SIX1-introduced SW480 cells compared with their empty vector-transfected counterparts.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Overexpression of SIX1 is observed in various types of cancer such as hepatocellular carcinoma (Ng et al, 2006), breast cancer (Kumar, 2009), ovarian cancer (Behbakht et al, 2007) and cervical cancer (Wan et al, 2008). In addition, overexpression of SIX1 is likely to be related to progression, invasion or metastasis in some cancers such as hepatocellular carcinoma (Ng et al, 2006) and breast cancer (Coletta et al, 2008), although understanding of the molecular mechanisms of SIX1 Figure 4 (a) ZEB1 and SNAI1 mRNA (left, bar graphs) and protein (right, western blotting) expression level in SIX1-introduced SW480 cells compared with their empty vector-transfected counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Through quantitative reverse transcription-PCR (RT-PCR) analysis, the results of our microarray-based analyses were validated in 11 genes (Supplementary Table S3). Based on these results, we focused on the SIX1 gene, because (a) SIX1 is known to be a transcriptional factor designating as a homeoprotein and essential for development of organs (Zheng et al, 2003;Kumar, 2009); and (b) altered expression of this gene is observed in various cancers (Ford et al, 1998;Ng et al, 2006;Behbakht et al, 2007;Coletta et al, 2008;Wan et al, 2008) and induces EMT in mammary cells (Micalizzi et al, 2009). Subsequent quantitative RT-PCR analysis of a panel of CRC cell lines showed that SIX1 mRNA expression is frequently positive (8/18 lines, 44%; Figure 1c).…”
Section: Six1 Gene Is a Putative Mesenchymal Marker In Crc Cellsmentioning
confidence: 99%
See 1 more Smart Citation
“…HKc/HPV16 represent freshly immortalized cells, whereas HKc/DR have been selected for resistance to differentiation and failure to growth arrest in response to TGF-ß (13). Whereas both cell lines are nontumorigenic, mRNA expression analysis has shown that HKc/DR are more similar to cervical carcinoma cells than HKc/HPV16 cells (14). As in our experiments with cervical cancer lines, we designated kinases as "essential candidates" when their depletion yielded ≥50% difference in proliferation/survival relative to HFKs.…”
Section: Identification Of Human Kinases That Become Important At Dismentioning
confidence: 99%
“…One homeobox gene of interest is the Six1 homeoprotein, which has an important role in the expansion of progenitor cell populations during early embryogenesis (Grifone et al, 2005) and is known to be essential for the development of numerous organs (Li et al, 2003;Zheng et al, 2003;Ozaki et al, 2004). In addition, Six1 is reported to be overexpressed in multiple pediatric and adult human cancers, including breast (Ford et al, 1998), ovarian (Behbakht et al, 2007), cervical (Wan et al, 2008) and hepatocellular carcinomas (Ng et al, 2006), as well as rhabdomyosarcomas and Wilms' tumors (Li et al, 2002;Yu et al, 2004). It is important to note that Six1 overexpression has been strongly associated with aggressive, metastatic cancers and poor prognosis (Coletta et al, 2004;Yu et al, 2004;Behbakht et al, 2007).…”
Section: Introductionmentioning
confidence: 99%